Kid’s online typing game (cabaran keyboard) - Nor Hazwani, Abdul Rahman (2015)
The use of information and communication technology (ICT) is so wide and covers every aspect of life. We have experience of children’s curiosity about computer, mobile phones, play station portable (PSP) games etc. Kindergarten students gained learning skills through interacting with multimedia contents. Moreover, multimedia has the potential to create high quality learning environments especially for children, with the capability of creating a more pragmatic learning context through its different medias- texts, graphics, sound, animation etc. Kid’s Online Typing Game (Cabaran Keyboard) is an educational game that is developed to improve the efficiency the kids typing. And also to make the kids know how to spell some words and understand the meaning of the words. This project is also developed to make the kids more exposed to technology.